2016
DOI: 10.1111/bjh.14041
|View full text |Cite
|
Sign up to set email alerts
|

TERT rs2736100 A>C SNP and JAK2 46/1 haplotype significantly contribute to the occurrence of JAK2 V617F and CALR mutated myeloproliferative neoplasms – a multicentric study on 529 patients

Abstract: Polycythaemia vera (PV), essential thrombocythaemia (ET) and primary myelofibrosis (PMF) represent typical myeloproliferative neoplasms (MPN), usually characterized by specific somatic driver mutations (JAK2 V617F, CALR and MPL). JAK2 46/1 haplotype and telomerase reverse transcriptase gene (TERT) rs2736100 A>C single nucleotide polymorphism (SNP) could represent a large fraction of the genetic predisposition seen in MPN. The rs10974944 C>G SNP, tagging the JAK2 46/1 haplotype, and the TERT rs2736100 A>C SNP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…The TERT rs2736100_C allele has recently been identified to be associated with increased risk of MPNs based on analyses of Caucasian patients [ 13 16 ]. This finding provides significant insights into genetic susceptibility to MPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TERT rs2736100_C allele has recently been identified to be associated with increased risk of MPNs based on analyses of Caucasian patients [ 13 16 ]. This finding provides significant insights into genetic susceptibility to MPN.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is likely unbiased, because there is no difference in the rs2736100 genotype distribution between males and females in the general population in Sweden or China. Information on association between gender and allele variant of TERT rs2736100 in MPN patients is lacking in the majority of published studies [ 14 16 ], but one study reported a similar variant distribution in men and women [ 13 ]. Among MPN patients, women have been reported to have superior survival compared to men [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JAK2 46/1 haplotype predisposes especially to JAK2 V617F‐mutated MPN, while rs2736100, located in the TERT (telomerase reverse transcriptase) gene, predisposes to all MPN, regardless of the clinical or molecular sub‐type . We previously replicated these findings in our patients …”
Section: Introductionmentioning
confidence: 99%
“…In particular, according to recent data in 2035 MPN patients, of which 356 with a diagnosis of polycythemia vera (PV), who were extensively genotyped for a number of single nucleotide polymorphisms (SNPs) associated with hematologic traits and/or diseases, the JAK2 46/1 haplotype was found to strongly associate with diagnosis of PV (hazard ratio, 2.3). Additional genetic variations predisposing to MPN were later described in MECOM , TERT and HBS1L‐MYB ; the combined effect of JAK2/TER/MECOM variants was estimated to have a population association rate of 51% for JAK2 ‐negative MPN …”
mentioning
confidence: 99%